Quality of Family Life and Workplace Deviant Behaviour with Perceived Competence as a Mediator among University Staff - A. Fagbenro, Dare; O. Olasupo, Mathew (Naše gospodarstvo/Our economy, 2020)
Several studies have found a variety of factors as antecedents of deviant behaviour but the role of family life on workplace deviant behaviour, as well as the mediating role of perceived competence in the quality of family life- deviant behaviour relationship, have received little study. This study examines the mediating effect of perceived competence on the relationship between the quality of family life and work-deviant behaviour. The study adopted the wellness model and self-determination theory as theoretical standpoints. Three hundred and eight-four (384) university staff in Nigeria participated in the study. Results revealed that there was a significant negative relationship between the quality of family life and workplace deviant behaviour. The result of the hierarchical multiple regression also revealed that perceived competence mediates the link between the quality of family life and workplace deviant behaviour. These findings suggest that psychologists should design training programmes aimed at improving the sense of competence and quality of family life, which invariably will reduce workplace deviant behaviour.
Keywords: quality of family life; perceived competence; workplace deviant behaviour; university employees